Palgrave Handbook of Research in Historical Culture and Education
XXIII, 856 p. 8 illus., 1 illus. in color.
Keywords: This volume comprises a broad interdisciplinary examination of the many different approaches by which contemporary scholars record our history. The editors provide a comprehensive overview through thirty-eight chapters divided into four parts: a) Historical Culture and Public Uses of History; b) The Appeal of the Nation in History Education of Postcolonial Societies; c) Reflections on History Learning and Teaching; d) Educational Resources: Curricula, Textbooks and New Media. This unique text integrates contributions of researchers from history, education, collective memory, museum studies, heritage, social and cognitive psychology, and other social sciences, stimulating an interdisciplinary dialogue. Contributors come from various countries of Northern and Southern America, Europe and Asia, providing an international perspective that does justice to the complexity of this field of study. The Palgrave Handbook of Research in Historical Culture and Education provides state-of-the-art research, focussing on how citizens and societies make sense of the past through different ways of representing it.